2013
DOI: 10.1088/1468-6996/14/2/023002
|View full text |Cite
|
Sign up to set email alerts
|

Oxide-based inorganic/organic and nanoporous spherical particles: synthesis and functional properties

Abstract: This paper reviews the recent progress in the preparation of oxide-based and heteroatom-doped particles. Surfactant-templated oxide particles, e.g. silica and titania, are possible candidates for various potential applications such as adsorbents, photocatalysts, and optoelectronic and biological materials. We highlight nanoporous oxides of one element, such as silicon or titanium, and those containing multiple elements, which exhibit properties that are not achieved with individual components. Although the mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 147 publications
(127 reference statements)
0
7
0
Order By: Relevance
“…Porous materials have been paid much attention in both scientific research and practical applications [2125]. For a catalyst support, a hierarchically porous structure and monolithic shape are more meaningful and desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Porous materials have been paid much attention in both scientific research and practical applications [2125]. For a catalyst support, a hierarchically porous structure and monolithic shape are more meaningful and desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Tagaya et al successfully prepared Eu(III)-doped nanoporous silica spheres by the sol–gel method and found that Eu 3+ ions were located in a low-symmetry environment [8]. Mukhametshina studied the effects of silica coating and further silica surface decoration by phospholipid bilayers on the quenching of Tb(III) complexes by adrenochrome [9]. Binnemans provided detailed information on certain materials, including sol–gel technology-based composites using silica precursors as the host matrix [10].…”
Section: Introductionmentioning
confidence: 99%
“…The size and morphology of the oxide structures affect the ability of these oxides to perform these varied functions. [1][2][3][4][5][6][7][8][9][10][11] Current industrial methods for forming inorganic oxides involve the use of organic solvents, corrosive pH, and/or high temperature and pressure. Though effective at producing the oxide, they provide limited control over morphology.…”
Section: Introductionmentioning
confidence: 99%